Facilities and Materials for Teaching Sewing in Junior High Schools in Selected Schools in Ghana - Akomaning, Esther Laurinda (Archives of Business Research, 2020)
The study explored the views of Junior High School teachers in an urban area in Ghana on instructional facilities and materials for teaching Sewing. Descriptive survey design was used to conduct the study and the objectives were to find out the instructional facilities and materials available and not available for teaching Sewing. Through purposive, cluster and systematic random sampling procedures, 78 teachers were sampled to participate in the study. Questionnaire and observation checklist were used to collect data. The data were analysed with SPSS to generate frequencies and percentage table. The results show that classrooms, basic tools such as needles, dress maker’s pins, pin cushion, scissors, tape measure, brown paper and BDT textbook were available. However, sewing machines, thimbles, seam rippers, fabrics, threads and cupboards/chest of drawers were not available in the schools to facilitate effective teaching and learning. For improvement, all stakeholders in education should help with the provision of teaching and learning resources for Sewing.